2015
DOI: 10.15406/htij.2015.01.00017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-A and Anti-B Alloisogglutinin Titer in Group O Plateletpheresis Donors

Abstract: Platelet (PLT) transfusions need to take into account the issues that arise due to significant amounts of ABO antigen being present on the platelets surface and anti-ABO alloisogglutinins being present in the donor's plasma. Although relatively rare, acute intravascular haemolytic transfusion reactions (AHTRs) have been caused by passive transfer of anti-A and anti-B antibodies, present in apheresis platelets (APs) of group O donors, across a minor ABO incompatibility (group A, B and AB recipients). To date, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A similar study by Mavichak et al conducted in same setting demonstrated some tendency of higher anti-A and anti-B titers in female than male though not statistically significant. 9 The age of the donor in present study was 18-60 years. In the present study, it has been shown that young population between 20-30-and 30-40-years age group showed high titre.…”
Section: Discussionmentioning
confidence: 82%
“…A similar study by Mavichak et al conducted in same setting demonstrated some tendency of higher anti-A and anti-B titers in female than male though not statistically significant. 9 The age of the donor in present study was 18-60 years. In the present study, it has been shown that young population between 20-30-and 30-40-years age group showed high titre.…”
Section: Discussionmentioning
confidence: 82%
“…This can quickly destroy the transfused platelets, causing poor post-transfusion platelet recovery. The second type is minor ABO-incompatibility, which occurs when the donor's plasma has antibodies against the recipient's ABO antigen on RBC [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In platelet transfusion, there are two types of ABO incompatibility [ 6 ]. The first is major incompatibility, which occurs when the recipient's plasma contains antibodies against the donor's ABO antigen on the platelets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations